Overjet and overbite analysis during the eruption of the upper permanent incisors. - Cuoghi, Osmar A; Sella, Rodrigo C; Mamede, Igo; de Macedo, Fernanda A; Miranda-Zamalloa, Yésselin M; Mendonça, Marcos Rogério de [UNESP] (My University, 2009)
ABSTRACT The purpose of this study was to analyze the overjet and overbite behavior during eruption of the upper permanent incisors. Fourth-eight plaster casts of 16 patients from ages 6-13 years were appraised longitudinally. It was found that the overjet remains constant, starting at the eruption of the upper permanent central incisors until eruption of the upper permanent canine teeth, while the overbite increases after eruption of the upper permanent lateral incisors and remains constant with the eruption of the canine teeth.
Keywords: adolescent; child; human; incisor; longitudinal study; malocclusion; pathophysiology; tooth eruption; Adolescent; Child; Humans; Incisor; Longitudinal Studies; Malocclusion; Tooth Eruption